Landscape degradation and desertification in the Mu Us Shamo, Inner Mongolia - an ecological and climatic problem since historical times? - Rost, Karl Tilman; Böhner, Jürgen (ERDKUNDE, 2003)
Extensive sand sheets and dunes are the dominant landforms throughout the semi-arid Mu Us Shamo, but are not in equilibrium with the modern climate. Previous studies indicated that dune formation mainly occurred during the last glacial period. However, these dunes and sand sheets have been intensively reworked by human intervention during several periods of Chinese land cultivation within the past 2,300 years. Large scale migration into this fragile steppe ecosystem and non-sustainable cultivation mainly occurred during the Western Han, the Tang, and Qing Dynasty, as well as during the period 1911-1980, leading to a conversion of nomadic pastoral systems to intensified cropping, environmental deterioration and desertification. In addition to this human impact, decade-scale historical droughts and cool-dry periods, characterized by an increased near-surface wind activity, must also be considered. Migration of Han-Chinese farmers into the eastern semi-arid regions of northern China often took place during moderately humid and temperate periods of strengthened summer monsoon influence. In contrast, emigration mainly occurred during relatively cooler and drier episodes, when the Mongolian-Siberian high-pressure cell was displaced to the south and winter monsoon winds and droughts strengthened. It is suggested that climate shifts favourable for increased sand supply and eolian activity additionally may have formed a basis for the historical sand reworking and desertification processes in the southern Ordos Plateau.